Risk factors of wall calcification in unruptured intracranial aneurysms - Costa, Leonardo; Kamphuis, Maarten J.; Akanji, Oluwadamilola; Schaaf, Irene C. van der; Kamp, Laura T. van der; Vergouwen, Mervyn D. I.; Etminan, Nima; Rinkel, Gabriel J. E. (Journal of neurosurgery, 2026)
OBJECTIVE Wall calcification in unruptured intracranial aneurysms (UIAs) increases the risk of complications of microsurgical aneurysm treatment. Therefore, information on wall calcification is important in deciding on the indication and modality of preventive treatment. However, wall calcification is often not visible on MR angiography. The authors studied risk factors for aneurysm wall calcifications to identify patients who should undergo preprocedural CT imaging to detect wall calcifications. METHODS From two international cohorts of patients with single or multiple UIAs, data were collected on age, sex, smoking status, hypertension, aneurysm location, aneurysm size, and morphological parameters associated with increased risk for rupture (i.e., at-risk morphology = aspect ratio > 1.6, size ratio > 3, presence of lobulations, and/or irregular shape). Logistic regression was used to calculate odds ratios (ORs) with corresponding 95% confidence intervals (CIs) to investigate risk factors for wall calcification. Using receiver operating characteristic analysis in one cohort, a size cutoff value was determined for ruling out aneurysm wall calcification, which was validated in the other cohort. RESULTS Two hundred fifty-five patients with 306 UIAs were included. In univariable analyses, risk factors of aneurysm wall calcification were aneurysm size (OR 1.2, 95% CI 1.1-1.3), hypertension (OR 2.1, 95% CI 1.1-4.5), and at-risk morphology (OR 2.4, 95% CI 1.3-4.4). In multivariable analysis, independent risk factors for wall calcification were aneurysm size (OR 1.2, 95% CI 1.1-1.3) and hypertension (OR 2.8, 95% CI 1.2-6.6), but not at-risk morphology (OR 1.3, 95% CI 0.7-2.7). Aneurysm wall calcification could be ruled out in more than 90% of aneurysms smaller than 6 mm in both the derivation and validation cohorts. CONCLUSIONS Aneurysm size and hypertension are independent risk factors of aneurysm wall calcification. The authors recommend preprocedural CT imaging in patients with a UIA ≥ 6 mm.